Reading Comprehension Skills of Grade 6 Pupils in the District of Ambaguio, SDO Nueva Vizcaya: Springboard for Reading Intervention - Serquiña, Shirley (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the reading comprehension skills of Grade 6 pupils in the District of Ambaguio, Schools Division Office of Nueva Vizcaya, as basis for a proposed reading intervention. Using a descriptive quantitative research design, the study examined the reading comprehension performance of 38 Grade 6 pupils selected through purposive sampling. Data were gathered through a reading comprehension test that measured the pupils’ skills in literal, inferential, and evaluative comprehension. The results revealed that the pupils obtained an overall mean score of 11.84 out of 20, indicating a moderate level of reading comprehension. In terms of reading comprehension level, 21.05% of the pupils were classified at the independent level, 44.74% at the instructional level, and 34.21% at the frustration level. Among the three dimensions, literal comprehension obtained the highest mean of 3.62, followed by inferential comprehension with 2.94, while evaluative or critical comprehension registered the lowest mean of 2.48. These findings indicate that although the pupils had developed basic text understanding, many still experienced difficulty in deeper comprehension processes. The study concluded that the respondents’ reading comprehension skills were still developing and that a reading intervention is needed, particularly for pupils under the instructional and frustration levels. It is recommended that a reading intervention program be developed with emphasis on strengthening inferential and evaluative comprehension through guided and differentiated reading activities.
Keywords: Ambaguio District, Grade 6 Pupils, Reading Comprehension, Reading Intervention, Reading Skills